An Investigation into the Subjectivity in Saudi Newspaper: Hard News from Appraisal Perspective - Alrobaye, Amani Abdullah (Journal of Humanities & Social Sciences, 2019)
This present study addresses the question of how the reporter's evaluated hard news and highlighted the type of news which was appraised mostly by the reporters. Particularly, it analyses the attitudes of the reporters of Saudi English newspaper. This research seeks to examine the hard news in particular. It adapts the critical analysis and the appraisal theory by (Martin & White, 2005) to investigate the data, which comprises 40 reports chosen randomly, posted during 2015-2016 as the most recent reports. The most important findings of this study show that a reporter employed different evaluating strategies while reporting hard news. These strategies could be illustrated by the following. Firstly, the occurrences of judgmental instances were the most frequent among other subsystems of attitude and formed 42.5%. While the Affect instances were formed 32.5% of the total, moreover, appreciative instances were detected apparently in the data but formed only 25%. Secondly, the instances of positive attitude were a bit more frequent than the negative attitude. On the other hand, regarding the directness of expressing reporters' attitudes were inscribed. Finally, which is the most interesting finding is that the reporters revealed their attitude extensively toward political report more than other types of hard news. This study strongly recommends that more writing courses for both academic and professional purposes are integrated into the training program of future news reporters.
Keywords: Saudi Arabia; Saudi Newspaper; Critical Discourse Analysis; Appraisal Approach; News Discourse; Newspaper Subjectivity